Stress Among Nurses working in Intensive Care Unit at Tertiary care Hospital, Nepal - Kumari Jha, Nilam; Koirala, Nabina; shah, Paammi; Pokhrel, Khushi; K.C., Nyamika; Dhami, Kabita (Birat Journal of Health Sciences, 2024)
Introduction: Stress is a major issue for intensive care unit (ICU) nurses due to their demanding work environment. They perform complex assessments, high-intensity treatments, and continuous care, dealing with intricate patient health issues and advanced technology. This constant high-pressure setting makes stress a persistent challenge for ICU nursing professionals.Objectives: This study aims to assess level of stress and its association with selected demographic variables among nurses working in the Intensive care at Tertiary care Hospital of Nepal.Methodology: A cross-sectional study was conducted at selected Tertiary care Hospital of Nepal, from July 2022 to March 2023. A total of 69 respondents were selected by using a nonprobability consecutive sampling technique. A self-administered questionnaire was used to gather the data and stress was assessed using the Expanded Nursing Stress Scale (ENSS). SPSS V 22 was used to analyse the data using descriptive and inferential statistical techniques.Results: The findings of the study revealed that out of 69 respondents, 88.4% of respondents reported moderate levels of stress followed by mild stress 7.2 %, whereas a very small number of respondents 4.3% had severe stress. There was significant association between stress and the type of family p =0.010.Conclusion: The study shows majority of the intensive care nurses has moderate level of stress, few has mild and severe level of stress. Thus the study concludes that the intensive care nurses are working in moderate stressful conditions.